2010
DOI: 10.3329/ptcb.v19i1.4987
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Regeneration through Apical and Axillary Shoot Proliferation of Ficus religiosa L. - A Multi-purpose Woody Medicinal Plant

Abstract: A protocol was established for mass propagation of the valuable medicinal plant Ficus religiosa L. (Moraceae) through in vitro culture using apical and axillary buds of young sprouts from selected plants. Best shoot induction was observed on MS basal medium supplemented with 0.5 mg/l BAP + 0.1 mg/l IAA, in which 78 per cent of the explants produced 16 shoots per culture. Repeated subcultures in the same medium, resulted rapid shoot multiplication with 24 shoots per culture. In vitro raised shoots rooted on hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
18
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 7 publications
5
18
2
Order By: Relevance
“…As compared to BAP alone in the medium, more shoot proliferation (nearly threefold) was observed when it was supplemented with 0.5 mg/l IAA. A similar synergistic effect of cytokininauxin combinations towards shoot proliferation has been reported earlier also (Mishra et al 2008;Negi and Saxena 2010;Hassan et al 2009). …”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…As compared to BAP alone in the medium, more shoot proliferation (nearly threefold) was observed when it was supplemented with 0.5 mg/l IAA. A similar synergistic effect of cytokininauxin combinations towards shoot proliferation has been reported earlier also (Mishra et al 2008;Negi and Saxena 2010;Hassan et al 2009). …”
Section: Discussionsupporting
confidence: 64%
“…In our study we found 1.0 mg/l of BAP as the most effective concentration for the shoot bud induction as well as shoot proliferation. Deshpande et al (1998), however, has reported 5 mg/l BAP as suitable for initial bud break and 1.0 mg/l BAP as for further shoot proliferation of Ficus religiosa, while Hassan et al (2009) found 0.5 mg/l BAP in combination with 0.1 mg/l IAA as most suitable for shoot multiplication. This difference in observations might be due to the differences in the basal medium, genotype, and physiological state as well as environmental conditions of the mother plant.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In vitro shoot regeneration has already been reported for F. religiosa (Jaiswal and Narayan 1985, Deshpande et al 1998, Hassan et al 2009, Siwach and Gill 2011, 2013. No report has been found in the literature on plant regeneration from immature-explants of F. religiosa.…”
mentioning
confidence: 97%